The Importance of Green Consumer Behavior as an Environmental Concern in Fast Food Restaurants - Wahid Muhammad Shodiq; Noor Harini; Rahayu Relawati (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This research aims to determine how green consumers behave when making purchases at fast food restaurants. Methodology – This study relies on primary data collected through the distribution of questionnaires to fast-food restaurant patrons in Malang Raya. The study included a total of 100 respondents and was descriptively evaluated. Findings – Compared to other product features, the product attributes connected with the eco-friendly program for fast-food restaurants gained a low average score. On the other hand, consumers' awareness of the importance of keeping the environment clean is strong. When selecting to buy at a fast food restaurant, customers demonstrate inconsistency by initially assessing their necessities. Green consumer behavior is only shown when consumer needs have been fulfilled. Environmental care actions are also shown by consumers after consuming, where consumers are responsible for waste or residual consumption through waste sorting and clean culture application. Originality – This study presents the behavioral responses of green consumers to various purchase considerations to provide another reference in making purchases at fast food restaurants.